Biodiversity mainstreaming for healthy & sustainable food systems: A toolkit to support incorporating biodiversity into policies and programmes - Hunter, D.; Borelli, Teresa; Olsen Lauridsen, N.; Gee, E.; Rota Nodari, Giulia; Moura de Oliveira Beltrame, Daniela; Oliviera, C.; Wasike, Victor W.; Samarasinghe, G.; Tan, A.; Güner, B. (Bioversity International, 2018)
The Biodiversity for Food and Nutrition Initiative (BFN Project) uses indigenous food biodiversity as a lens to address malnutrition, farmer livelihood resilience, and sustainability. Since 2012, the initiative has pioneered a cross-sectoral, partner-based approach to document and share information on 195 nutrient-rich, locally-adapted species ranging from African leafy vegetables to Amazonian fruits. Spearheaded by governments and research organizations in Brazil, Kenya, Sri Lanka, and Turkey, BFN developed a three-pronged methodology to ensure the conservation, revival, and promotion of these underutilised species.